Laparoscopic Surgeries in Urology: Initial Burgeoning Experience at National Transplant Centre, Nepal - Katwal, B. M.; Koju, S.; Junwar, K. J.; Shrestha, D.; Verma, R.; Shrestha, P. C. (Kathmandu University Medical Journal, 2021)
Background This study focuses on experience of laparoscopic surgery at Shahid Dharma Bhakta National Transplant Centre (SDNTC), Nepal; which could enable us to gain knowledge regarding its benefits over conventional surgery. The present study revealed the frequency of various forms of laparoscopic surgeries done at our centre. Moreover, this study accomplishes laparoscopic donor nephrectomy “a historical milestone achieved in Nepal for kidney transplantation on 18th November 2018” which was the first Laparoscopic donor nephrectomy done in Nepal by Nepalese team. Objective The present study assesses the feasibility and safety of laparoscopic surgery at government hospital of Nepal. Method This hospital based cross-sectional study included all patients of age group 10 to 60 years, coming to outpatient department of SDNTC and those having indications for nephrectomy. We excluded patient having previous history of open surgeries of kidney, bleeding disorders, uncontrolled Diabetes Mellitus and uncontrolled Hypertension. The study duration was 15 months from November 2017 to January 2019. The total number of patients enrolled in the study was fifty where transperitoneal laparoscopic surgery was performed in all 50 patients. The demographic data, indications for surgery, duration of surgery, complications of surgery and perioperative outcomes were analyzed. Result Out of 50 cases, 34 (68%) underwent simple lap nephrectomy, 6 (12%) were lap pyeloplasty, 6 (12%) lap nephrectomy along with ureterectomy of long segment of diseased ureter, 1 (2%) lap radical nephrectomy, 1 (2%) lap donor nephrectomy for kidney transplantation, 1 (2%) lap heminephrectomy and 1 (2%) lap nephrectomy for hydronephrotic non functioning left crossed ectopia. Amongst all nephrectomies, 27 (54%) patients were operated on right side while 23 (46%) patients on left. The median age of the patient was 38.56 years. Out of total cases 32 (64%) were male and 18 (36%) female. The median operative time and hospital stay was 122.3 minutes and 5 days respectively. The median estimated blood loss was 74.1 cc. Only one patient required blood transfusion intra-operatively. 2 (4%) patients were converted to open surgery. Conclusion Laparoscopic surgery is feasible and safe procedure in government setup hospital with less cumbersome procedure and minimum complications associated with it.